ANALISIS PENGGUNAAN MEDIA DIGITAL TERHADAP INTERAKSI SOSIAL IBU RUMAH TANGGA DI DESA LAUT DENDANG KECAMATAN PERCUT SEITUAN - Dedek Fadila Tri Julianta Tarigan; Adam Tbn; Rasenda; Ester Piani Telaumbanua; Lara Sungam Br Ginting; Maharani Cheche Kiranti; Mutiara Seven Manalu; Marcella Pebrina Br Tarigan; Ibnu Hajar; Anifah (STKIP Subang, 2026)
The development of digital technology has significantly influenced patterns of social interaction within society, including among housewives. The increasing use of smartphones and social media platforms such as WhatsApp, Facebook, and Instagram has transformed communication patterns into more practical and efficient forms. This study aims to analyze the use of digital media on the social interactions of housewives in Desa Laut Dendang, Kecamatan Percut Sei Tuan. This research employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The subjects of this study involved 20 housewives living in Gang Manalu, Desa Laut Dendang. The findings indicate that digital media usage does not entirely reduce direct social interaction within the community. Most respondents continue to actively engage in face-to-face communication, participate in social activities, and maintain harmonious social relationships with surrounding communities. Furthermore, differences in social interaction patterns were found between housewives living in densely populated neighborhood areas and those residing in residential complexes. Housewives in neighborhood areas tend to have stronger direct social interactions due to higher social solidarity and more open communication patterns. Therefore, digital media functions primarily as a supporting communication tool rather than replacing direct social interaction in community life.